2007
DOI: 10.1111/j.1095-8339.2007.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of Narcissus serotinus L. s.l. (Amaryllidaceae) in the Iberian Peninsula

Abstract: A morphological study of Narcissus serotinus L. s.l. was carried out in 40 populations, mainly located in the southwest Iberian Peninsula, by the application of ordination and classification analysis to 42 vegetative and flower characters. Wide morphological variability was found in the species. A total of 19 characters clearly differentiated two groups as distinct species, but intraspecific variation, associated with geographical distribution, was found. One of the species aligned with N. serotinus L. s.s. , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
3
26
0
1
Order By: Relevance
“…5A), as denoted by the medians of between-group F st values (0.61) being significantly greater than the medians of withingroup F st distributions (0.40). In addition, the virtual absence of admixed individuals in the mountain range where the green and blue groups occur in sympatry (Cazorla-Segura-Las Villas) suggests that despite instances of hybridization being known for this genus (Blanchard 1990;Díaz-Lifante and Andrés-Camacho 2007;Marques et al 2007Marques et al , 2010Díaz-Lifante et al 2009) and the occasional co-occurrence of plants from both groups in adjacent habitats within this area, some type of reproductive isolation between them may be operating. Fifth, the comparison of the relationship between genetic and geographic distances revealed substantial differences between the within-and between-group regression lines ( fig.…”
Section: And Partial Mantel Tests Testing For Associations Between Pamentioning
confidence: 93%
See 1 more Smart Citation
“…5A), as denoted by the medians of between-group F st values (0.61) being significantly greater than the medians of withingroup F st distributions (0.40). In addition, the virtual absence of admixed individuals in the mountain range where the green and blue groups occur in sympatry (Cazorla-Segura-Las Villas) suggests that despite instances of hybridization being known for this genus (Blanchard 1990;Díaz-Lifante and Andrés-Camacho 2007;Marques et al 2007Marques et al , 2010Díaz-Lifante et al 2009) and the occasional co-occurrence of plants from both groups in adjacent habitats within this area, some type of reproductive isolation between them may be operating. Fifth, the comparison of the relationship between genetic and geographic distances revealed substantial differences between the within-and between-group regression lines ( fig.…”
Section: And Partial Mantel Tests Testing For Associations Between Pamentioning
confidence: 93%
“…The taxonomy of Narcissus is unsettled and problematic (Webb 1980;Blanchard 1990;Mathew 2002;Zonneveld 2008;Aedo, forthcoming); in particular, the trumpet daffodils (section Pseudonarcissi) are one of the most controversial groups of the genus and are a clear example of the confounding views on both the discrimination of taxa and the assignment of rank (see below). In fact, the reasons for this wide discrepancy among studies may reflect, among other processes, recent phylogenetic divergence, ongoing differentiation, high phenotypic plasticity, hybridization, or some complex combination of these (Pérez- Barrales et al 2006;Díaz-Lifante and Andrés-Camacho 2007;Hodgins and Barrett 2007;Díaz-Lifante et al 2009). Irrespective of the mechanisms responsible for this complexity, however, tracing species boundaries in such complex groups is a challenge unless the patterns and causes of differentiation are assessed.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous attempts at a Narcissus classification have been published, but the genus has never been properly monographed (but see Haworth, 1831 and Pugsley, 1933). Problems faced by taxonomists are mostly related to the biological features of Narcissus , such as continuous speciation via incomplete morphological differentiation across populations of some species, hybridization and polyploidy (Fernandes, 1968, 1975; Webb, 1980; Brandham & Kirton, 1987; Díaz Lifante & Andrés Camacho, 2007). Chromosome studies carried out by Fernandes (1951, 1968, 1975) have allowed a better understanding of the nature of hybrids, many of them being virtually sterile (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Knowing the amounts of nuclear DNA this was easy to spot, especially so, as these are all three autumn flowering species. Lifante and Camacho (2007) did extensive morphological measurements on these taxa and concluded that, apart from the two parents a third form, a hybrid, was involved. They did not refer to the earlier work of Donnison-Morgan et al (2006).…”
Section: Genus Narcissusmentioning
confidence: 99%
“…The systematic value of nuclear DNA content for all species of Narcissus L. (Amaryllidaceae) 111 The systematic value of nuclear DNA content for all species of Narcissus L. (Amaryllidaceae) 113 The systematic value of nuclear DNA content for all species of Narcissus L. (Amaryllidaceae) 115 The systematic value of nuclear DNA content for all species of Narcissus L. (Amaryllidaceae) 117 (Lifante and Camacho 2007). However this application is doubtful as they do not make a distinction between the diploid hybrid N. 9 obsoletus (N. elegans 9 N. serotinus) ( Table 2) found as solitary specimen amidst its parents in Morocco (Maire 1959) and its widespread tetraploid form N. miniatus (Table 1).…”
Section: Genus Narcissusmentioning
confidence: 99%